Pearl Harbor: Japan's attack and America's entry into World War II - Melber, Takuma (Polity, 2021)
I. The background -- The road to Pearl Harbor -- The crisis intensifies -- Japan's proposals for resolving the conflict -- The Hull Note -- II. The Japanese war plan -- Admiral Yamamoto and Operation Hawaii -- The plan of attack -- The Kidō Butai sets sail -- Japanese spies in Hawaii -- The first encounter -- III. The attack -- The first wave -- 'Tora Tora Tora' -- Battleship Row in crossfire -- The second attack wave -- Egusa's dive bombers -- IV. Consequences -- The aftermath -- The USA enters the war -- The first prisoner-of-war -- The Japanese-born victims of Pearl Harbor -- Could Pearl Harbor have been prevented? -- Conspiracy theories -- Operation K.